Influence of solid nontransparent inclusion shape on the breakup time of heterogeneous water drops; International Communications in Heat and Mass Transfer; Vol. 101 - Antonov D. V. Dmitry Vladimirovich; Vysokomornaya O. V. Olga Valeryevna; Piskunov M. V. Maksim Vladimirovich; Fedorenko R. M. Roman Mikhaylovich; Yan Wei Mon (2019, 2019)
Title screen